1:1 FASTA update: Using the power of E-values in FASTA to detect potential allergen cross-reactivity. (2015) - Song, Ping; Herman, Rod; Kumpatla, Siva
Abstract: In the context of regulatory assessment of transgenic proteins for potential allergenicity, a previous investigation demonstrated that a 1:1 FASTA comparison using an E -value of 1.0E-09 as a criterion is superior to the conventional FASTA search (using the whole sequence as a query) for >35% identity over 80 amino acids, but with improved specificity. A further study, using groups of known cross-reactive peanut allergens, indicates the sensitivity of this approach is superior to the conventional FASTA search and equivalent to 80-mer sliding window FASTA search recommended by WHO/FAO. Specifically, the 1:1 FASTA approach eliminated the technical issues resulting from lack of identification of short query sequences with high identity to known allergens, or high identity over short amino acid stretches, and different E -value settings when searching for >35% identity over 80aa. Based on the performance of this simple application of existing bioinformatics tools, and its ease of implementation and interpretation in the context of a regulatory assessment, we advocate that adoption of this 1:1 FASTA approach as a supplement to the FAO/WHO/ CODEX criterion (>35% identity over 80aa) formulated 13 years ago. Adoption of this approach eliminates many biologically irrelevant homology hits generated by the FAO/WHO/CODEX criterion and improves the safety assessment of GM crops.